Aseptic production of citric and isocitric acid from crude glycerol by genetically modified Yarrowia lipolytica. (January 2019) - Rzechonek, Dorota A.; Dobrowolski, Adam; Rymowicz, Waldemar; Mirończuk, Aleksandra M.
Highlights: Overexpression of GUT1/GUT2 allow for aseptic production of organic acids. Crude glycerol is a proper substrate for efficient isocitric acid production. Aseptic conditions for organic acid synthesis were established. Abstract: The unconventional yeast Yarrowia lipolytica is known for its capacity to produce citric or isocitric acid from glycerol. In this study a reduction of production cost was achieved by using cheap crude glycerol and conducting the production at pH 3 to prevent bacterial contamination. In this study a Y. lipolytica strain overexpressing Gut1 and Gut2 was used. For the modified strain, crude glycerol proved to be an excellent substrate for production of citric/isocitric acids in aseptic conditions, as the final concentration of these compounds reached 75.9 ± 1.8 g L −1 after 7 days of batch production. Interestingly, the concentration of isocitric acid was 42.5 ± 2.4 g L −1, which is one of the highest concentrations of isocitric acid obtained from a waste substrate. In summary, these data show that organic acids can be efficiently produced by the yeast Y. lipolytica from crude glycerol without any prior purification in aseptic conditions.